The art of less : how to focus on what really matters at work - Alvesson, Mats, 1956-; Spicer, André (London ; New York ; Oxford ; New Delhi ; Sydney : Bloomsbury Business, 2025)
At work we often feel weighed down by an excess of initiatives, meetings, training and targets. Over-enthusiastic executives, interfering consultants and demanding stakeholders often get in the way of doing the 'real work'. This leaves us feeling overwhelmed but underproductive. The Art of Less offers ideas for how to create a more effective and efficient organization by removing obstacles to meaningful work. Mats Alvesson and André Spicer explain how 'organizational sludge' gets in the way of performance, and what can be done about it. They show how unblocking systems and processes can improve work flow so people can focus more on the things that actually matter.
Kniha se zabývá problémem nadměrné zátěže moderních organizací, množstvím iniciativ, schůzek, školení a administrativních procesů, které brání soustředění na smysluplnou práci. Autoři představují koncept tzv. organizačního „sludge“, tedy překážek snižujících výkonnost a efektivitu, a ukazují, jak je možné tyto bariéry systematicky odstraňovat. Publikace nabízí praktické i analytické přístupy ke zjednodušování pracovních procesů, zlepšování toku práce a vytváření prostředí, v němž se zaměstnanci mohou více zaměřit na činnosti, které mají skutečný význam
Obsahuje bibliografické odkazy a rejstřík
Keywords: organizace práce; racionalizace; organizační chování; procesní management; monografie; work design; rationalization; organizational behavior; process management; monographs